Wage flexibility in ongoing employment relations: an experiment with a stochastic labor market - Siegfried K. Berninghaus; Sabrina Bleich; Werner Güth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Facing a stochastic market wage, which is independent of their own hiring policy, employers offer contracts specifying fixed wage, revenue share and employment duration. In ongoing employment relations it depends on the treatment whether fixed wages can be only increased or also decreased. Will the uncertainty of the future market wage and less wage flexibility lead to temporary employment? And, if not, will employers adjust wages to changing market wages and will workers in ongoing employment relations react to wage decreases via effort choices? Our results partly question empirical claims, e.g. of Bewley (1995), and confirm the tendency to establish ongoing employment relations. Granting more wage flexibility to employers altogether questions rather than enhances efficiency since it induces opportunistic wage cuts to which employees react with lower efforts.
Keywords: C72; C90; F16; J21; J24; L10; 330; noncooperative game; labor contracts; labor market flexibility; principalagent theory; experimental economics; Lohnstruktur; Arbeitsvertrag; Arbeitsbeziehungen; Agency Theory; Nichtkooperatives Spiel; Arbeitsmarktflexibilisierung; Test